UPAYA MENINGKATKAN MINAT BELAJAR SISWA DALAM PEMBELAJARAN SENI TARI MELALUI MEDIA AUDIO VISUAL PADA KELAS VII/2 SMP NEGERI 1 PAINAN - Eggy Hennike Putri; Zora Iriani; Fuji Astuti (SENDRATASIK UNP, 2018)
Abstract This article aims to reveal the increasing interest in student learning towards the learning dance arts through the use of audio-visual media in 7th-grade students SMP Negeri 1 Painan. This type of research was classroom action research. This research was conducted using two cycles; each cycle consisted of planning, implementing, observing, and reflecting. Techniques of data collection were carried out by observation, documentation and test techniques. The data obtained in the study were analyzed using qualitative and quantitative data analysis. Based on the results of the study, it can be concluded that the learning of dance art in 7th-grade students SMP Negeri 1 Painan with Tari Piring (Dance by using glass plate) materials previously experienced a decrease in the value of KKM and learning interest from students. Recommendations from the results of the study where there was an increase in student interest per cycle as much as in the first cycle there was an increase of 28.13% and in the second cycle, there was an increase in interest by 27.03%. Overall, the effect of the teacher's actions using the audiovisual media has been quantitatively increasing at 55.16%. It can be seen that from 21 students who did not achieve the KKM score from the dance activity now there are only 4 students who have not achieved the KKM score, but the value continues to increase from its initial value. The impact of the actions of cultural arts teachers using audio-visual media has increased the attention, desire, and participation of students in participating in learning dance art in 7th-grade students SMP Negeri 1 Painan. Keywords:                 The Effort, Interest In Learning The Art, Dance, Audio Visual